Accumulation of arsenic and antimony in Aloe barbadensis: A transplantation study - Ong, Ghim Hock; Cheng, Wan Hee; Wong, Ling Shing (Wiley Online Library, 2018)
Arsenic (As) and antimony (Sb) accumulation in medicinal plants is a serious health issue, especially in common plants such as Aloe barbadensis. The accumulation of As and Sb in A. barbadensis is assessed in this study by transplanting A. barbadensis in a control and contaminated soil plot. Samples of A. barbadensis and surface soils from both control (Nilai, Malaysia) and polluted (Klang, Malaysia) sites were collected and analyzed for heavy metals using neutron activation analysis. Indices used to assess the anthropogenic input of this study were the index of geoaccumulation (Igeo) and enrichment factor (EF), while the metals uptake of the plant were determined using the bioconcentration factor (BCF) and translocation factor (TF). Overall, Klang soils showed higher As and Sb concentrations compared to Nilai. The EF of As were 19.38 for Nilai and 28.07 for Klang while the EF of Sb was 18.01 for Nilai and 29.12 for Klang. These values indicated significant enrichment (EF: 5–20) for Nilai and moderate enrichment (EF: 20–50) for Klang. The Igeo values for As were 3.25 (Nilai) and 3.89 (Klang) while the Igeo values for Sb were 3.14 (Nilai) and 3.94 (Klang), which fell under the category of “strongly polluted” (Igeo: 3–4). The BCF for As ranged from 0.05 to 0.07 while Sb was recorded at 0.07, indicating only small amounts of As and Sb were transferred from the soil to the roots. TF for As ranged from 0.29 to 0.67 while TF for Sb ranged from 0.51 to 0.89, showing a high percentage of metals transfer from roots to shoots. This study concluded that As and Sb levels in A. barbadensis were not harmful for human consumption.